To solve for x in the equation −4(2x−11)=12, we can simplify the equation first:
−4(2x−11)=12
Distribute the -4 to the terms inside the parentheses:
-8x + 44 = 12
Next, we can subtract 44 from both sides of the equation:
-8x = 12 - 44
-8x = -32
To solve for x, we divide both sides of the equation by -8:
x = (-32) / (-8)
The division of -32 by -8 gives us:
x = 4
Therefore, the solution for x is x = 4.
Solve for x.
−4(2x−11)=12
(1 point)
Responses
x=−2
x equals negative 2
x=4
x equals 4
x=2
x equals 2
x=−4
9 answers
Solve for x.
−3(−4x−3)=−27
(1 point)
Responses
x=−3
x equals negative 3
x=−2
x equals negative 2
x=2
x equals 2
x=3
−3(−4x−3)=−27
(1 point)
Responses
x=−3
x equals negative 3
x=−2
x equals negative 2
x=2
x equals 2
x=3
To solve for x in the equation −3(−4x−3)=−27, we can simplify the equation first:
−3(−4x−3)=−27
Distribute the -3 to the terms inside the parentheses:
12x + 9 = -27
Next, we can subtract 9 from both sides of the equation:
12x = -27 - 9
12x = -36
To solve for x, we divide both sides of the equation by 12:
x = (-36) / 12
The division of -36 by 12 gives us:
x = -3
Therefore, the solution for x is x = -3.
−3(−4x−3)=−27
Distribute the -3 to the terms inside the parentheses:
12x + 9 = -27
Next, we can subtract 9 from both sides of the equation:
12x = -27 - 9
12x = -36
To solve for x, we divide both sides of the equation by 12:
x = (-36) / 12
The division of -36 by 12 gives us:
x = -3
Therefore, the solution for x is x = -3.
Solve for x: 2x−4x−3=−27.(1 point)
Responses
x=4
x equals 4
x=−4
x equals negative 4
x=−12
x equals negative 12
x=12
Responses
x=4
x equals 4
x=−4
x equals negative 4
x=−12
x equals negative 12
x=12
To solve for x in the equation 2x−4x−3=−27, we can combine like terms on the left side of the equation:
2x - 4x - 3 = -27
Simplify by combining the x terms:
-2x - 3 = -27
Next, we can add 3 to both sides of the equation:
-2x = -27 + 3
-2x = -24
To isolate x, we divide both sides of the equation by -2:
x = (-24) / (-2)
The division of -24 by -2 gives us:
x = 12
Therefore, the solution for x is x = 12.
2x - 4x - 3 = -27
Simplify by combining the x terms:
-2x - 3 = -27
Next, we can add 3 to both sides of the equation:
-2x = -27 + 3
-2x = -24
To isolate x, we divide both sides of the equation by -2:
x = (-24) / (-2)
The division of -24 by -2 gives us:
x = 12
Therefore, the solution for x is x = 12.
Solve for x: −4(3x+10)−2=54.(1 point)
Responses
x=4
x equals 4
x=8
x equals 8
x=−4
x equals negative 4
x=−8
Responses
x=4
x equals 4
x=8
x equals 8
x=−4
x equals negative 4
x=−8
To solve for x in the equation −4(3x+10)−2=54, we can simplify the equation first:
−4(3x+10)−2=54
Distribute the -4 to the terms inside the parentheses:
-12x - 40 - 2 = 54
Combine like terms:
-12x - 42 = 54
Next, we can add 42 to both sides of the equation:
-12x = 54 + 42
-12x = 96
To isolate x, we divide both sides of the equation by -12:
x = (96) / (-12)
The division of 96 by -12 gives us:
x = -8
Therefore, the solution for x is x = -8.
−4(3x+10)−2=54
Distribute the -4 to the terms inside the parentheses:
-12x - 40 - 2 = 54
Combine like terms:
-12x - 42 = 54
Next, we can add 42 to both sides of the equation:
-12x = 54 + 42
-12x = 96
To isolate x, we divide both sides of the equation by -12:
x = (96) / (-12)
The division of 96 by -12 gives us:
x = -8
Therefore, the solution for x is x = -8.
Solve for x: 20x−5(6x+15)=−45.(1 point)
Responses
x=−2
x equals negative 2
x=2
x equals 2
x=−3
x equals negative 3
x=3
Responses
x=−2
x equals negative 2
x=2
x equals 2
x=−3
x equals negative 3
x=3
To solve for x in the equation 20x−5(6x+15)=−45, we can simplify the equation first:
20x - 5(6x+15) = -45
Distribute the -5 to the terms inside the parentheses:
20x - 30x - 75 = -45
Combine like terms:
-10x - 75 = -45
Next, we can add 75 to both sides of the equation:
-10x = -45 + 75
-10x = 30
To isolate x, we divide both sides of the equation by -10:
x = (30) / (-10)
The division of 30 by -10 gives us:
x = -3
Therefore, the solution for x is x = -3.
20x - 5(6x+15) = -45
Distribute the -5 to the terms inside the parentheses:
20x - 30x - 75 = -45
Combine like terms:
-10x - 75 = -45
Next, we can add 75 to both sides of the equation:
-10x = -45 + 75
-10x = 30
To isolate x, we divide both sides of the equation by -10:
x = (30) / (-10)
The division of 30 by -10 gives us:
x = -3
Therefore, the solution for x is x = -3.